The Teaching of Filipino thru the modified four-pronged approach as assessed by the elementary Filipino teachers in the division of lipa city - Enriquez, Fernando B. (Manila : National University, 2007)
The study covered 66 elementary schools in the Division of Lipa City, Lipa City. Accordingly, 122 primary teachers and 78 intermediate teachers from these schools were considered as respondents.
Approval Sheet -- Acknowledgement -- Dedication -- Table of contents -- List of tables -- Abstract -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Methodology -- Chapter 4. Presentation, analysis, and interpretation of data -- Chapter 5. Summary, Conclusion, and recommendation -- Bibliography -- Appendices.
Research Method : Descriptive Method.
Includes bibliographical references.